Characteristics of intracranial aneurysms in the else kröner-fresenius registry of autosomal dominant polycystic kidney disease - Neumann, Hartmut P. H. (2012)
Background Patients who harbor intracranial aneurysms (IAs) run a risk for aneurysm rupture and subsequent subarachnoid hemorrhage which frequently results in permanent deficits or death. Prophylactic treatment of unruptured aneurysms is possible and recommended depending on the size and location of the aneurysm as well as patient age and condition. IAs are major manifestations of autosomal dominant polycystic kidney disease (ADPKD). Current guidelines do not suggest surveillance of IAs in ADPKD except in the setting of family history if IA was known in any relative with ADPKD. Management of IAs in ADPKD is problematic because limited data exist from large studies. Methods We established the Else Kröner-Fresenius Registry for ADPKD in Germany. Clinical data were assessed for age at diagnosis of IAs, stage of renal insufficiency, and number, location and size of IAs as well as family history of cerebral events. Patients with symptomatic or asymptomatic IAs were included. All patients with ADPKD-related IAs were offered mutation scanning of the susceptibility genes for ADPKD, the PKD1 and PKD2 genes. Results Of 463 eligible ADPKD patients from the population base of Germany, 32 (7%) were found to have IAs, diagnosed at the age of 2?71 years, 19 females and 13 males. Twenty (63%) of these 32 patients were symptomatic, whereas IAs were detected in an asymptomatic stage in 12 patients. IAs were multifocal in 12 and unifocal in 20 patients. In 26 patients (81%), IAs were diagnosed before end-stage renal failure. Twenty-five out of 27 unrelated index cases (93%) had no IAs or cerebral events documented in their relatives with ADPKD. In 16 unrelated index patients and 3 relatives, we detected germline mutations. The mutations were randomly distributed across the PKD1 gene in 14 and the PKD2 gene in 2 index cases. Questionnaires answered for 320/441 ADPKD patients without IAs revealed that only 45/320 (14%) had MR angiography. Conclusion In ADPKD, rupture of IAs occurs frequently before the start of dialysis, is only infrequently associated with a family history of IAs or subarachnoid hemorrhage, and is associated with mutations either of the PKD1 or the PKD2 gene of any type. Screening for IAs is widely insufficiently performed, should not be restricted to families with a history of cerebral events and should be started before end-stage renal failure.